158Prediction of diabetes and hypertension by opportunistic screening: A facility based study from rural Jodhpur. (2nd September 2021) - Gupta, Manoj Kumar; Raghav, Pankaja; Bhardwaj, Pankaj; Rustagi, Neeti; KH, Naveen; Goel, Akhil D; Thirunavukkarasu, Prasanna; Sharma, Prem Prakash
Abstract: Background: Nearly half of population with Diabetes and Hypertension is estimated to be undetected in India. The objectives of this study were to conduct opportunistic screening for Diabetes and Hypertension coming to OPD of health centres under Department of Community Medicine and Family Medicine, AIIMS Jodhpur, India and to develop the models for prediction of Diabetes and Hypertension. Methods: Time bound study was conducted at three rural health centres between 2018-19. A total of 942 patients aged ≥30 years were screened. Data was recorded using Epicollect5. Risk assessment was done by using Indian Diabetes risk score (IDRS), Community based assessment checklist (CBAC), Waist Hip Ratio, & BMI. Random and fasting capillary blood sugar and BP was measured. Results: The mean age of the participants was 52.4 ± 13.5 years. As much as 446 (47.4%) had IDRS score of ≥ 60 and 276 (29.3%) had CBAC score of ≥ 4. RBS level of ≥ 140mg/dl was found among 223 participants, of these, 42.5% were diagnosed to be diabetic on FBS. One-fourth (25.6%) were estimated to be hypertensive. Physical activity and hypertension were best predicting the diabetes (r 2 = 90.8), while hypertension was best predicted by age and BMI (r 2 = 74.3). Conclusions: Prevalence of diabetes and hypertension was in accordance with the reported prevalence in the country. As compared to existing models, less number of prediction variables were identified for NCDs. Key messages: The study highlights the need for implementation of hospital based opportunistic screening and point out the necessity to revise the existing prediction models for NCDs.